Task-Related Reorganization of Functional Connectivity in Early Detection of Consciousness in Patients With Severe Brain Injury - A.S, Zigmantovich; L.B, Oknina; M.M, Kopachka; E.L, Masherow; E.V, Alexandrova (Archives of Clinical and Biomedical Research, 2019)
In recent years the number of patients with early postcomatosis long-term states of unconsciousness is increasing in the world. Accurate assessment of current functional state of patients in unconscious states is very important for correct treatment strategy and rehabilitation activities especially in cases when the difference between those states is not clinically obvious. To investigate features of resting-state wavelet synchrony in unconscious patients with severe brain injury and how TMS-therapy can affect resting state functional connectivity. We used stimulus-based EEG paradigm to detect changes of functional connectivity after TMS-therapy. Fifteen patients were recruited. They had the diagnosis of minimally conscious state (MCS) (male = 9, female = 2; n = 11), vegetative state/unresponsive wakefulness syndrome (VS/UWS) (male = 4, n = 4). We analyzed functional connectivity, values of wavelet synchrony in resting state and for responses on stimuli of patients before and after TMS-therapy. Of the 15 patients, eleven (eight MCS, two VS/UWS) had positive clinical dynamics including improvement of moving, emergence of glance fixation and gaze tracking, speech understanding and attempts of speech productions. The appearance of interhemispheric and diagonal connections is a favorable prognostic sign. TMStherapy makes it possible to include activate functional networks in resting state.